2022
DOI: 10.1093/nar/gkac460
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic labeling of DNA methylation patterns for single-molecule epigenetic mapping

Abstract: DNA methylation, specifically, methylation of cytosine (C) nucleotides at the 5-carbon position (5-mC), is the most studied and significant epigenetic modification. Here we developed a chemoenzymatic procedure to fluorescently label non-methylated cytosines in CpG context, allowing epigenetic profiling of single DNA molecules spanning hundreds of thousands of base pairs. We used a CpG methyltransferase with a synthetic S-adenosyl-l-methionine cofactor analog to transfer an azide to cytosines instead of the nat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 55 publications
0
25
0
4
Order By: Relevance
“…The short recognition site of a methyltransferase has been used to generate dense labels, so-called amplitude modulation profiles, along the DNA backbone (Grunwald et al, 2015) and methyltransferasebased labeling was utilized to obtain high-resolution optical maps also by Jeffet et al (2016). By combining nick labeling protocols with methyltransferase-based labeling hybrid genetic/epigenetic maps, providing both genomic and methylation profiles simultaneously, can be obtained, as illustrated by Sharim et al (2019) and Gabrieli et al (2022).…”
Section: Enzyme-based Labelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The short recognition site of a methyltransferase has been used to generate dense labels, so-called amplitude modulation profiles, along the DNA backbone (Grunwald et al, 2015) and methyltransferasebased labeling was utilized to obtain high-resolution optical maps also by Jeffet et al (2016). By combining nick labeling protocols with methyltransferase-based labeling hybrid genetic/epigenetic maps, providing both genomic and methylation profiles simultaneously, can be obtained, as illustrated by Sharim et al (2019) and Gabrieli et al (2022).…”
Section: Enzyme-based Labelingmentioning
confidence: 99%
“…The latter has recently been demonstrated (Torstensson et al ., 2021), as briefly discussed above. Alternatively, labeling to obtain genetic information can be combined with other types of labels, such as epigenetic markers (Sharim et al ., 2019; Margalit et al ., 2020; Gabrieli et al ., 2022) or labeling of DNA damage (Müller et al ., 2019), thereby adding an additional layer of information to the optical DNA map. The development of labels that can be used to obtain such additional information that is not yet accessible remains a challenge in ODM.…”
Section: Optical Dna Mappingmentioning
confidence: 99%
“…CpG methyltransferases are blocked when the cytosine is methylated, and thus will label only um-CpGs (Figure 2a). We and others have shown that a double mutant of the CpG-specific DNA MTase M.Sssl can label unmodified cytosines with azide groups via the AdoYnAzide cofactor 37,38 . However, M.Sssl is difficult to express at high concentrations and it tends to aggregate upon expression.…”
Section: -Methylcytosine (5mcmentioning
confidence: 99%
“…Using fluorescence microscopy and designated chemistries, OGM can provide multilayered information from individual DNA molecules. Fluorescent labeling of different genomic features with different colors allows studying multiple epigenetic marks on the single-molecule level, creating a hybrid genetic/epigenetic map for every DNA molecule (19, 23, 24, 26).…”
Section: Introductionmentioning
confidence: 99%